Intrafamilial Role Changes and the Process of Overcoming Identity Crisis of Paternal Characters in German and Thai Novels - Techaphan, Atthaphon (Journal of Letters, 2018)
This article focuses on the problems of identity and paternal roles experienced by paternal characters in German and Thai novels published after 1990. The analysis discusses how new facets of fatherhood, which are the result of the interchange of family roles between men and women and of the increased prevalence of single-parent families, are problematized on the fictional level. The study details the struggles of paternal characters to adjust to their newly assigned roles, to associate themselves with these roles, their alienation from society and the conflict between the male identity and the changing condition in being a father. Struggles to adjust are presented more frequently in German novels than their Thai counterparts. It is noticeable that paternal characters fail to acknowledge the reorganization of intrafamilial roles; to be exact, they are deprived of role distance, the capability to discern between personal identity as a male and social identity as an egalitarian father.